2017
DOI: 10.1038/ni.3837
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of T follicular regulatory cell responses by interleukin 2 during influenza infection

Abstract: SUMMARY Interleukin 2 (IL-2) promotes Foxp3+-regulatory T (Treg) cell responses, but inhibits T follicular helper (TFH) cell development. However, it is not clear how IL-2 affects T follicular regulatory (TFR) cells, a cell type with properties of both Treg and TFH cells. Using an influenza infection model, we demonstrated that high IL-2 concentrations at the peak of the infection prevented TFR cell development by a Blimp-1–dependent mechanism. However, once the immune response resolved, some Treg cells down-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
298
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(328 citation statements)
references
References 54 publications
17
298
1
Order By: Relevance
“…[12][13][14]35 However, some other groups have shown that the lack of Tfr cells had no impact on GC size and GC B-cell numbers. In different murine models, absence of Tfr cells led to expansion of Tfh and GC B cells, as well as increased antibody production.…”
Section: Definiti On Of T Follicul Ar Line Ag Ementioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14]35 However, some other groups have shown that the lack of Tfr cells had no impact on GC size and GC B-cell numbers. In different murine models, absence of Tfr cells led to expansion of Tfh and GC B cells, as well as increased antibody production.…”
Section: Definiti On Of T Follicul Ar Line Ag Ementioning
confidence: 99%
“…In different murine models, absence of Tfr cells led to expansion of Tfh and GC B cells, as well as increased antibody production. [35][36][37][38][39] Thus, it was suggested that Tfr cells impose a more stringent competition for Tfh help on GC B cells, promoting the generation of high affinity antibodies, while limiting the overall expansion of antigen-specific B-cell clones. 36 The impact of Tfr cells on the regulation of antigen-specific B cells and antibody affinity was also addressed.…”
Section: Definiti On Of T Follicul Ar Line Ag Ementioning
confidence: 99%
See 1 more Smart Citation
“…68 Therefore, IL-2 in the local microenvironment is essential to determine the fate of CD4 + T cell differentiation. 73 The interplay between IL-2 and TFR needs further studies. 71 The suboptimal IL-2 signaling in T1D not only reduced the number, but also impaired the function of Treg cells.…”
Section: Suboptimal Il-2 Signalingmentioning
confidence: 99%
“…The clustering together of TFH-like cells and FoxP3 + Helios + regulatory T cells further raises the possibility that T follicular regulatory cells are also present 43,44 . A distinct set of effector CD4 + T cells could be …”
Section: Cc-by-nc-nd 40 International Licensementioning
confidence: 99%